2004
DOI: 10.1002/cncr.20062
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility antigens and antigen‐processing molecules in retinoblastoma

Abstract: BACKGROUNDMalignant transformation of cells is frequently associated with abnormalities in human leukocyte antigen (HLA) expression. These abnormalities may play a role in the clinical course of the disease, because HLAs mediate interactions of tumor cells with cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells. Retinoblastoma is the most common intraocular malignant tumor in childhood and is characterized by direct spread to the optic nerve and orbit as well as hematogeneous and lymphatic spread. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…These studies suggested that downregulation of HLA-I (i.e., mixed or negative HLA-I expression) might reflect the escape of malignant cells from human immune system. On the other hand, other studies reported that cancers with downregulated HLA-I were correlated with early tumor stage and better prognosis including breast cancer [9], uveal melanoma [12], non-small cell lung cancer [14], and colorectal cancer [17]. These results reflect the controversy about the exact role of HLA-I expression in malignancies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These studies suggested that downregulation of HLA-I (i.e., mixed or negative HLA-I expression) might reflect the escape of malignant cells from human immune system. On the other hand, other studies reported that cancers with downregulated HLA-I were correlated with early tumor stage and better prognosis including breast cancer [9], uveal melanoma [12], non-small cell lung cancer [14], and colorectal cancer [17]. These results reflect the controversy about the exact role of HLA-I expression in malignancies.…”
Section: Discussionmentioning
confidence: 78%
“…In recent years, reduced or loss of HLA-I expression has been reported to be associated with tumor development or patients' outcome in breast cancer [8][9][10], malignant melanoma [11,12], laryngeal carcinoma [13], small cell carcinoma of the lung [14], ovary carcinoma [15], cervical carcinoma [16], and colorectal cancer [17]. However, the relation of HLA-I, especially heavy chain of HLA-I, expression with patients' outcome in gastric cancer has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Loss of tapasin expression is a frequent event that has been reported in a wide variety of human cancers, including malignant melanoma, head and neck squamous cell carcinoma (HNSCC), renal cell carcinoma, colorectal carcinoma, glioblastoma, lung carcinoma, and neuroblastoma. [10][11][12][13][14][15][16][17][18] Notably, tapasin expression associated with intratumoral T-cell infiltration has been reported as a prognostic marker of patient survival in ovarian carcinoma, HNSCC, glioblastoma, and colorectal carcinoma. 12,13,[19][20][21] It is also reported that loss of tapasin is more frequent among the other antigen-processing machinery (APM) components, strongly suggesting its central role in escape from CTL immune surveillance to tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated loss of all the components of the PLC and other gene products involved in antigen presentation occurs in retinoblastoma [91], colorectal carcinoma [92] and in a mouse model of metastatic fibrosarcoma [93].…”
Section: Tap Genes and Malignancymentioning
confidence: 99%